Eight gastropods new for the marine fauna of Madeira. - Wirtz, Peter (2008)
The prosobranchs Architectonica nobilis and Smaragdia viridis and the opisthobranchs Arminia maculata, Cyerce cf. graeca, Elysia papillosa, Petalifera petalifera, Pleurobranchaea meckeli and Pleurobranchus testudinarius are recorded from Madeira Island for the first time.